Early diagnostic evaluation of miR-122 and miR-224 as biomarkers for hepatocellular carcinoma - Khalda S. Amr; Hanan Abd Elmawgoud Atia; Rehab Abd Elazeem Elbnhawy; Wafaa M. Ezzat (Genes and Diseases, 2017)
Hepatocellular carcinoma (HCC) is one of the common lethal types of tumor all over the world. The lethality of HCC accounts for many reasons. One of them, the lack of reliable diagnostic markers at the early stage, in this context, serum miRNAs became promising diagnostic biomarkers. Herein, we aimed to identify the predictive value of two miRNAs (miR-122 and miR-224) in plasma of patients with HCC preceded by chronic HCV infection. Taqman miRNA assays specific for hsa-miR-122 and hsa-miR-224 were used to assess the expression levels of the chosen miRNAs in plasma samples collected from three groups; 40 patients with HCC related to HCV, 40 with CHC patients and 20 healthy volunteers. This study revealed that the mean plasma values of miRNA-122 were significantly lower among HCC group when compared to CHC and control groups (P < 0.001). Whereas, miR-224 mean plasma values were significantly higher among HCC group when compared to both CHC group and control group. Moreover, it was found that miR-122 can predict development of HCC at cut-off value <0.67 (RQ) and (AUC = 0.98, P < 0.001). As regards miR-224, it can predict development of HCC at cut-off value >1.2 (RQ) and (AUC = 0.93, P < 0.001), while the accuracy of AFP to diagnose HCC was (AUC: 0.619; P = 0.06). In conclusion, the expression plasma of miR-122 and miR-224 could be used as noninvasive biomarkers for the early prediction of developing HCC at the early stage.